ANALISIS KEPUASAN PASIEN FARMASI RAWAT JALAN MENGGUNAKAN METODE SERVQUAL(STUDI KASUS DI RUMAH SAKIT SWASTA X JAKARTA) - Yuliati, Yuliati; Magdalena, Eliza; Daniar, Daniarpratiwi (Indonesian Journal of Nursing Health Science, 2016)
AbstractCurrently, Indonesias health development began to emphasize on improving the quality of health care, where service quality should be oriented to customer satisfaction in order to continue to exist in the midst of global competition. Pharmacy Unit at X Hospital Jakarta is one of the medical support required to deliver a quality service that oriented to patient satisfaction.This research is descriptive study using primary data that obtained from the questionnaire that distributed to 400 patients at Outpatient Pharmacy, which in Outpatient Pharmacy for the patient who secured by insurance (A and B) and Cash (F). The category of patients at Outpatient Pharmacy are patient that secured by corporate, corporate pensioner in Jabodetabek, patient that secured by other insurance and cash patient. The sampling technique used is nonprobability sampling, the quota sampling. The level of satisfaction of patients seen by SERVQUAL method in five dimensions, that is responsiveness, empathy, reliability, assurance and tangible, as well as mapping the dimensions of service quality and its attributes in a Cartesian Diagram.In general, patients are not satisfied with the performance of Outpatient Pharmacy at X Hospital Jakarta. The results on the whole respondents for the gap between patients expectation and Outpatient Pharmacy X Hospitalsâ performance is negative. The sequence of the biggest negative gap felt in responsiveness (-0.7100), empathy (-0.6550), reliability (-0.5800), assurance (-0.4975) and tangible (-0.4200). The sequence of the greatest dissatisfaction felt by corporate pensioner in Jabodetabek (30.59%), cash patients (29.08%), patient that secured by other insurance (22.22%) and patient that secured by corporate (18.11%). The sequence of the biggest dissatisfaction perceived by the patient for services in Outpatient Pharmacy F (37.49%), Outpatient Pharmacy A (32.47%) and Outpatient Pharmacy B (30.04%). Based on the mapping of Cartesian Diagram, Outpatient Pharmacy at X Hospital Jakarta should pay more attention to the dimensions of responsiveness, especially regarding speed of service and providing more crew at peak hours.Â Keywords: Quality of Service, Satisfaction, SERVQUAL, Cartesian Diagram